Significance of new membrane formation in peritoneal biopsies of peritoneal dialysis patients: a case–control study - Kazuho Honda (Renal Replacement Therapy, 2017)
Abstract Background Newly formed membrane (NFM) on the peritoneal membrane proper is a unique pathological hallmark of encapsulating peritoneal sclerosis (EPS), but its definition and diagnostic significance have not been well described. This study investigated the pathological features of NFM in EPS and prevalence of NFM in peritoneal biopsy at catheter removal. Methods This multicenter retrospective, observational study was conducted by the Japanese Society of Peritoneal Dialysis and enrolled ten patients with and 52 without EPS at peritoneal biopsy during enterolysis surgery or catheter removal. All patients were treated using conventional, acidic peritoneal dialysis (PD) solutions. Thirty of the 52 non-EPS patients perform peritoneal lavage once daily after completing PD to prevent the development of EPS and 22 discontinued PD without lavage. NFM was defined as additional membrane structure on the peritoneum that is properly characterized by exudative or fibrous matrices and fibroblast-like cells. Immunostaining of fibrin and podoplanin was performed for the evaluation of NFM. Results NFM was confirmed histologically in eight of the ten patients with EPS. It was also detected in 13 of the 30 patients (43.3%) in the post-PD lavage group and in one of the 22 patients (4.5%) in the non-lavage group. The NFM histology showed various stages of EPS pathology, from early exudative changes with fibrin deposition (stage I; n = 5), progressing to proliferative and fibrosing changes with podoplanin-positive fibroblast-like cells (stage II; n = 9), and finally resulting in adhesive and fibrous scar formation (stage III; n = 8). Immunostaining of fibrin and podoplanin was helpful for evaluating the stage of the NFM. Conclusions NFM contributes the encapsulation of intestines and is a pathological hallmark of EPS, but can be detected microscopically in patients without EPS, especially those with peritoneal lavage after PD. New membrane formation starts insidiously in peritoneal membrane damaged by PD treatment, but does not necessarily lead to the development of EPS.